“Archbishop” Vladimir (Ivanov) and the renovationist schism in Kuban in 1941–1945 - Toporov Maxim, Priest (Вестник Свято-Филаретовского института)
The appeal to this topic is conditioned by the following factors: the increased interest of the Russian state and society in the Church and the frequent attempts to bring schism and disorder into the Church. The study of the regional component in the history of Renovationism allows the researcher to better understand the processes that took place in the schism, and it is also possible to identify historical facts related to a particular region, going beyond the generally accepted course of the history of the movement. Renovationism in the Kuban region during the years of war experienced a certain rise, on a par with the canonical Church. During the occupation of Krasnodar, the Renovationists had an advantage over the Tikhonovites with respect to “Bishop” Vladimir (Ivanov), while the canonical diocese had not had a bishop since 1937. The representatives of Renovationism in Kuban had certain contacts with the German administration, including the head of the Renovationist diocese, Vladimir (Ivanov). In contrast to the neighbouring regions, Renovationism was not persecuted in Kuban, possibly because of Ivanov’s cooperation with representatives of the occupation regime. At the same time, the article suggests that Ivanov may have worked with the Soviet authorities during the occupation, as records show that after the liberation of Krasnodar he was awarded the medal “For Valiant Labour”. In December 1944 Vladimir (Ivanov) repented and was appointed to the Krasnodar cathedra as a canonical bishop in January 1945. In many respects it became possible due to the petition of local authorities, besides it shouldn’t be forgotten that Ivanov had considerable authority in Kuban.